Training secondary school students as anti-smoke ambassadors using the service-learning model: A cluster randomized controlled trial with hybrid type 1 effectiveness-implementation design study protocol - Lam, Katherine Ka Wai; Ho, Ka Yan; Leung, Doris Yin Ping; Wong, Arkers Kwan Ching; Wu, Cynthia Sau Ting; Liu, Charlotte Qi; Mao, Ting; Mak, Yim Wah (PloS one, 2024)
Evidence shows that using the AWARD (Ask, Warn, Advise, Refer, Do-it-again) model with service-learning model in youngsters may be an appropriate strategy to refer young smokers for early smoking cessation services. Therefore this study aims to promote smoking cessation by training secondary school students as anti-smoke ambassadors (ASAs) with increased knowledge, skills and self-efficacy on smoking cessation and AWARD model using service-learning model. A cluster randomized controlled trial will be conducted in 14 secondary schools in Hong Kong. Also, a hybrid type 1 effectiveness-implementation design with the Reach Effectiveness Adoption Implementation Maintenance (RE-AIM) framework will be adopted. For the intervention group, participants (n = 184) will attend a 3-hour training workshop, followed by hands-on sessions supervised by trained nursing students, then a 6-month smoker referral competition and an award presentation ceremony. The control group (n = 184) will only attend the 3-hour training workshop. The research assistant will contact participants at the start and the end of training program, and at 3, 6, and 12 months after the end of the training program by telephone to complete a set of questionnaires. Participating secondary schools, participating nursing students, ASAs, and responsible organizational staff will be randomly invited for a one-to-one semi-structured interview. The primary outcome will be the number of smokers who referred by secondary school students. Descriptive statistics, mixed between-within-subjects ANOVA, logistic regressions, and content analysis will be used. This study will bridge the gap in existing literature by determining the effectiveness and exploring facilitators and barriers in implementing our intervention with the use of the AWARD model and service-learning model in training young people to refer smokers to anti-smoke organizations in the real-world. This can enhance our community capacity and enable youngsters to take a proactive role to support smoking cessation. ClinicalTrials.gov, NCT05897346. Registered on 11 May 2023.